2017
DOI: 10.3233/jad-170128
|View full text |Cite
|
Sign up to set email alerts
|

Concordance Between Cerebrospinal Fluid Biomarkers with Alzheimer’s Disease Pathology Between Three Independent Assay Platforms

Abstract: This study confirms strong concordance between CSF biomarkers and PET Aβ-amyloid status is independent of immunoassay platform, supporting their utility as biomarkers in clinical practice for the diagnosis of AD and for participant enrichment in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…The significant change in CSF Ab42 before the Ab PET threshold for Ab positivity (Fig 2) is in agreement with previous studies showing that CSF Ab42 becomes abnormal prior to Ab PET (Palmqvist et al, 2016Vlassenko et al, 2016). Further, the later change in Ab42/40 compared to Ab42 might be one of the explanations for the higher agreement between (dichotomous) Ab PET and Ab42/40 compared with Ab PET and Ab42 (Fig 2), which has been reported previously (Janelidze et al, 2016Lewczuk et al, 2017;Doecke et al, 2018). Although this temporal difference in Ab42 and Ab42/40 is in agreement with the spline model showing an initial drop in Ab40 followed by stable levels (Fig 3A), the A-D The biomarker data were fitted using monotone spline models for CSF Ab42 (A), Ab42/40 (B), P-tau (C), and T-tau (D) assays, where Ab PET SUVR acted as a proxy for time in AD.…”
Section: Discussionsupporting
confidence: 91%
“…The significant change in CSF Ab42 before the Ab PET threshold for Ab positivity (Fig 2) is in agreement with previous studies showing that CSF Ab42 becomes abnormal prior to Ab PET (Palmqvist et al, 2016Vlassenko et al, 2016). Further, the later change in Ab42/40 compared to Ab42 might be one of the explanations for the higher agreement between (dichotomous) Ab PET and Ab42/40 compared with Ab PET and Ab42 (Fig 2), which has been reported previously (Janelidze et al, 2016Lewczuk et al, 2017;Doecke et al, 2018). Although this temporal difference in Ab42 and Ab42/40 is in agreement with the spline model showing an initial drop in Ab40 followed by stable levels (Fig 3A), the A-D The biomarker data were fitted using monotone spline models for CSF Ab42 (A), Ab42/40 (B), P-tau (C), and T-tau (D) assays, where Ab PET SUVR acted as a proxy for time in AD.…”
Section: Discussionsupporting
confidence: 91%
“…It has been well established that the decreases in CSF Aβ42 coincide with increased brain amyloid plaque pathology (Seeburger et al, 2015; Doecke et al, 2018). In CSF, Aβ changes were detected before the changes in t-Tau in cognitively normal adults (Buchhave et al, 2012), and the change could be observed as early as middle-age (Sutphen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Strong concordance has been observed between CSF markers (Aβ 42 , tau, and pTau181) and PET-Aβ-amyloid status, as measured by the Roche Elecsys and INNOtest assays [ 30, 31 ]. A high correlation of CSF biomarkers on the AlzBio3 and EUROIMMUNE platforms has also been reported [ 101 ]. Methodologically, no difference in these biomarkers was observed from CSF collected using gravity or aspiration techniques [ 102 ].…”
Section: Resultsmentioning
confidence: 98%